A National Survey: Current Clinical Practice in Pediatric Anesthesia for Congenital Heart Surgery. Issue 3 (May 2020) - Baehner, Torsten; Kiefer, Nicholas; Ghamari, Shahab; Graeff, Ingo; Huett, Christopher; Pflugradt, Stefan; Sendzik, Bjoern; Heinze, Ingo; Mueller, Matthias; Schindler, Ehrenfried; Duerr, Georg Daniel; Ellerkmann, Richard; et al.
Background: Providing anesthesia for pediatric patients undergoing congenital cardiac surgery is complex and requires profound knowledge and clinical experience. Prospective studies on best anesthetic management are missing, partially due to different standards. The aim of the present study was to survey the current standard practice in anesthetic management in pediatric cardiac surgical centers in Germany. Methods: All 78 cardiac surgical centers in Germany were reviewed for a congenital cardiac surgery program. Centers with an active program for congenital cardiac surgery were interviewed to participate in the present online questionnaire to assess their current anesthetic practice. Results: Twenty-seven German centers running an active program for congenital heart surgery were identified, covering more than 3, 000 pediatric cardiac surgeries annually. Of these centers, 96.3% (26/27) participated in our survey. Standard induction agents were etomidate in 26.9% (7/26), propofol in 19.2% (5/26), a combination of benzodiazepines and ketamine in 19.2% (5/26), and barbiturates in 11.5% (3/26). General anesthesia was preferentially maintained using volatile agents, 61.5% (16/26), with sevoflurane being the most common volatile agent within this group, 81.2% (13/16). Intraoperative first-choice/first-line inotropic drug was epinephrine, 53.8% (14/26), followed by milrinone, 23.1% (6/26), and dobutamine 15.4% (4/26). Fast-track programs performing on-table extubation depending on the type of surgical procedure were established at 61.5% (16/26) of the centers. Conclusion: This study highlights the diversity of clinical standards in pediatric cardiac anesthesia for congenital cardiac surgery in Germany.